This Is Your Miḥrāb: Sacred Spaces and Power in Early Islamic North Africa—Al-Qayrawān as a Case Study - Albarrán, Javier (Religions, 2023)
Al-Qayrawān has long been figured, especially in the culture of the Islamic West, as the Islamic city par excellence, as the fourth sacred place after Mecca, Medina, and Jerusalem. The prominence of this garrison city—supposedly founded by ‘Uqba b. Nāfi‘ in the year 50/670–671—is undeniable in the traditional account of the Islamic conquest of Ifrīqiyya. Through a case study of al-Qayrawān and an analysis of the sources recounting its miraculous foundation as well as the construction of its mosque, this article aims to study the process of sacralisation of space, how this is inserted into a given context and related to power and its consolidation, particularly in times of political, cultural, and religious transition, and how it uses, appropriates, or eliminates the previous reality. To this end, the article provides a context for the creation of al-Qayrawān as a sacred space, which relates directly to the region’s Christian past and the construction of a new Islamic identity.